Family Empowerment Model in Stunting Prevention Based on Family Centered Nursing - Luluk Fauziyah Januarti; Alvin Abdillah; Agus Priyanto (Universitas STRADA Indonesia, 2020)
This study used an explanative survey design followed by descriptive study of the cross sectional approach, which was carried out with 2 stages. The first stage of the study was conducted by identifying internal and external factors for stunting prevention with family empowerment. The second stage involves conducting Focus Group Discussion (FGD) and expert discussion then devised a model of family empowerment as a stunting prevention effort. The number of respondents used was 280 families. The sampling techniques was using cluster sampling. The strongest indirectly data which obtained from the research analysis of the pathway to prevent stunting was extenal factors through stunting empowerment with value of 0.264. The second strongest indirect influence was for stunting prevention through internal stunting prevention factors with value of 0.114. The results of this study showed that the indirect influence of family empowerment on stunting prevention is not as strong as the direct influence